Konsep dan Teori Nutrisi serta Nutrisi yang Dibutuhkan Tubuh: Systematic Literature Review (SLR) - Nida An Hafiah; Nur Salsabila Lintang; Nuricha Octavia; Siti Aisyah Rambe (INDO PUBLISHING, 2026)
Nutrition is a basic human need that plays an important role in maintaining health, growth, development, and body functions. This study aims to examine the concepts and theories of nutrition as well as the types of nutrients needed by the body using the Systematic Literature Review (SLR) method. The research was conducted by collecting and analyzing various scientific literature sources such as journals, books, and academic articles relevant to the research topic. The results of the study show that nutrition consists of macronutrients and micronutrients that complement each other in maintaining body balance. Macronutrients include carbohydrates, proteins, and fats, while micronutrients consist of vitamins and minerals. In addition, water is also an important component in the body's metabolic processes. Nutrition has various important functions such as producing energy, supporting growth, repairing body tissues, maintaining the immune system, and helping metabolic processes. Therefore, balanced nutrition is very important to maintain health and improve human quality of life.